Identificações e escolhas profissional na adolescência:um estudo psicanalítico - Costa, Juvaneide Regia Azevedo (2013)
This work seeks to understand the difficulties and dilemmas that pervade the career choice of teenagers. For this, we take investigative via psyquic unconscious determinations that, as observed in present clinical practice, it is also confirmed important in the reviewed literature. In the last one, the most important findings signaled an important relationship between identification processes and the various choices we make throughout life. These findings led us to question about how psychoanalysis understands these processes and how they are involved in building the career choice of teenagers. From the referential Freudian and Lacanian, we have studied the concepts of adolescence and identification, which articulated the process of career choice and fragments of clinical cases, allowed us to reach conclusions that point to the deep involvement of the dimension of desire and the unconscious in issues regarding career choices and the possibility of building a listening, of the difficulties found there, more attentive to the psychic determinations and singular responses that each presents in front of these determinations